Chemomechanical caries removal - Perić Tamara; Marković Dejan (Serbian Medical Society - Dental Section, Belgrade, 2003)
The purpose of this paper was to introduce Carisolv™ system for chemo-mechanical caries removal and its main characteristics, mechanism of action, clinical procedure and the efficacy of this alternative method. New materials and technical and technological development contributed to more precise and efficient work in dentistry. However, problems of rotary instruments for caries removal have remained. Chemomechanical method for caries removal was introduced thirty years ago as an alternative to the conventional mechanical instruments. The technique involved applying a solution onto the carious tissue, allowing it to soften and to remove it without use of drill. Its advantages were: selective removal of carious tissue, absence of pain, reduced need for local anesthesia and reduced potential negative effects to the dental pulp.